2017
DOI: 10.1128/aac.00912-17
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Analysis of Multidrug-Resistant Escherichia coli from North Carolina Community Hospitals: Ongoing Circulation of CTX-M-Producing ST131- H 30Rx and ST131- H 30R1 Strains

Abstract: Escherichia coli sequence type 131 (ST131) predominates globally among multidrug-resistant (MDR) E. coli strains. We used whole-genome sequencing (WGS) to investigate 63 MDR E. coli isolates from 7 North Carolina community hospitals (2010 to 2015). Of these, 39 (62%) represented ST131, including 37 (95%) from the ST131-H30R subclone: 10 (27%) from its H30R1 subset and 27 (69%) from its H30Rx subset. ST131 core genomes differed by a median of 15 (range, 0 to 490) singlenucleotide variants (SNVs) overall versus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
44
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 42 publications
3
44
0
Order By: Relevance
“…This is consistent with global trends that suggest that the highly drug-resistant E. coli ST131, associated with the bla CTX-M- 15 gene, has been increasing in prevalence. [9][10][11] [15][16][17][18] There is some subtle structure within ST131, with isolates from this study that are primarily localized on a branch with a longer internal branch length, which may suggest the seeding and expansion locally in central Malawi ( Figure 1 ). Another difference from previous work is the higher number of ST410 isolates in this study, which carried the bla CTX-M-15 gene at the highest frequency of all the sequence types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is consistent with global trends that suggest that the highly drug-resistant E. coli ST131, associated with the bla CTX-M- 15 gene, has been increasing in prevalence. [9][10][11] [15][16][17][18] There is some subtle structure within ST131, with isolates from this study that are primarily localized on a branch with a longer internal branch length, which may suggest the seeding and expansion locally in central Malawi ( Figure 1 ). Another difference from previous work is the higher number of ST410 isolates in this study, which carried the bla CTX-M-15 gene at the highest frequency of all the sequence types.…”
Section: Discussionmentioning
confidence: 99%
“…[14] CTX-M-15 is strongly associated with ST131. [15][16][17][18] The global spread of ESBL-E. coli is largely attributed to the dissemination of E. coli strains carrying the bla CTX-M- 15 gene, especially E. coli O25b:H4-ST131. [11] Previously, three major lineages of ST131 were identified that differed mainly based on their fimH alleles: A (mainly fimH41), B (mainly fimH22) and C (mainly fimH30).…”
Section: Introductionmentioning
confidence: 99%
“…Previous work, mainly including isolates from North America, suggested that the H 30-R/C1 clade of ST131 most commonly carry IncF type F1:A2:B20 plasmids and the H 30-Rx/C2 clade are associated with IncF type F2:A1:B-plasmids. 17-19 In this cohort, plasmid types were associated with different sub-lineages of ST131. For instance, IncF type F31:A4:B1 or F36:A4:B1 plasmids were most frequently seen in clade C2, whereas IncF type F2:A1:B-were only seen in a single clade C1 strain.…”
Section: Discussionmentioning
confidence: 83%
“…8 Specific Incompatibility (Inc) F-type plasmids have also been described in association with fluoroquinolone-resistant ST131- H 30 clades, with IncF type F1:A2:B20 plasmids associated with the H 30-R/C1 clade and IncF type F2:A1:B-plasmids associated with the H 30-Rx/C2 clade. 17-19…”
Section: Introductionmentioning
confidence: 99%
“…Also, AMR among E. coli is increasingly reported for fluoroquinolones and third- and fourth-generation cephalosporins. Sequence type 131 (ST131) predominates globally among such MDR E. coli strains [11].…”
Section: Introductionmentioning
confidence: 99%